2022
DOI: 10.1007/s10943-022-01512-w
|View full text |Cite
|
Sign up to set email alerts
|

Rules We Live by: How Religious Beliefs Relate to Compliance with Precautionary Measures Against COVID-19 in Tibetan Buddhists

Abstract: The present studies investigated how particular religious beliefs shape compliance with preventive measures in adherents of Gelug and Nyingma schools of Tibetan Buddhism. In Study 1, Gelug and Nyingma monks were asked to report their compliance with various infection prevention measures surrounding COVID-19. Results showed that the former group showed higher compliance with public health guidelines than the latter. Extending beyond self-report measures, Study 2 added a behavioral outcome measure and observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Following Li (2021) and Li and Cao (2022) , all measures were implemented by research assistants who were unaware of the present study’s true hypotheses. The confederate greeted participants on the ground floor and provided them with a summary of the steps that were used in the survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Li (2021) and Li and Cao (2022) , all measures were implemented by research assistants who were unaware of the present study’s true hypotheses. The confederate greeted participants on the ground floor and provided them with a summary of the steps that were used in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a wealth of empirical studies have revealed that a variety of physical, psychological, social, and environmental factors systematically influence how people comply with protective behaviors during COVID-19 ( de León-Martínez et al, 2020 , Li, 2021a , Li, 2021b , Hartmann and Müller, 2022 , Tepe and Karakulak, 2023 ). For example, emerging findings from psychological research show that culture plays an important role in individuals’ abidance to COVID-19-related public health measures ( Chen and Biswas, 2022 , Gokmen et al, 2021 , English et al, 2022 , Jovančević and Milićević, 2020 , Li and Cao, 2022 ). For example, based on data sets from the Google community mobility reports regarding how communities move around differently, and from the Hofstede’s culture dimensions of 58 countries during the early phase of COVID-19, Huynh (2020) found that people in countries with higher level of uncertainty avoidance were more likely to adopt practices of social distancing even controlling for nuisance variables, such as wealth status and GDP per capital.…”
Section: Introductionmentioning
confidence: 99%
“…According to aforementioned ideas and findings, it appears that people's beliefs about the COVID-19 pandemic are malleable and flexible, influenced by a rich variety of factors ( Li, 2021 ; Li & Cao, 2022 ; Serpas & Ignacio, 2021 ). Thus, a good knowledge of the risk of contagion may require integrating a complex structure of many diverse and even contradictory inputs ( Anderson et al, 2020 ; Clark et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%